A kind of polymer-doped aluminum hydride hydrogen storage material and preparation method thereof
By doping polymer PMMA in aluminum hydride hydrogen storage materials, forming composite materials and performing high-pressure curing treatment, the shortcomings of aluminum hydride hydrogen storage materials in air stability and hydrogen release temperature are solved, and more efficient hydrogen storage and release.
Patent Information
- Application Number
- CN202310211385.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-07
AI Technical Summary
The existing aluminum hydride hydrogen storage materials have shortcomings in air stability and hydrogen release temperature, which are difficult to meet the needs of efficient hydrogen storage.
Using a polymer doping method, light metal hydrides (such as AlH3) and polymers (such as PMMA) are mechanically ball milled to form composite materials, and are made into a wafer through high-pressure curing to improve the space utilization and air of the material. stability.
It effectively reduces the initial hydrogen discharge temperature from 140℃ to 110℃, enhances the air stability performance, and simplifies the process, which is suitable for large-scale industrial production.
Smart Images

Figure CN116101974B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage materials, in particular to a polymer-doped aluminum hydride hydrogen storage material and a preparation method thereof. Background Art
[0002] As a new type of clean energy that is developing rapidly in the 21st century, hydrogen energy has attracted widespread attention from countries around the world. Hydrogen energy is a secondary energy source that is clean, environmentally friendly, has high energy density, and is flexible and diverse in its use. It can be used as an effective carrier of large-scale renewable energy. However, the large-scale use of hydrogen energy is still subject to many constraints. Among them, the high-density and safe storage of hydrogen is one of the bottleneck technologies that restrict the use of hydrogen energy. At present, there are three main types of relatively mature hydrogen storage technologies, namely high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage, and solid-state hydrogen storage. Hydrogen storage materials have the advantages of large volume hydrogen storage density, high safety, convenient transportation, and easy operation. It is a hydrogen storage method with great application prospects in the future. At present, the most widely used solid-state hydrogen storage materials include hydride hydrogen storage materials such as LiBH4, LiAlH4, LiNH2, and AlH3, and liquid materials include inorganic ammonia, organic hydrazine, hydrocarbons, carboxylic acids or alcohols.
[0003] AlH3 is a high-performance hydrogen storage material with potential, which has attracted the attention of researchers in the field of hydrogen storage. The thermal decomposition temperature of AlH3 is 150~200℃, and the dehydrogenation temperature can be further reduced after modification. In recent years, with the rise of hydrogen energy and fuel cell research, aluminum hydride has also received more and more attention. AlH3 has a high weight and volume hydrogen density of 10.1 wt.% and 0.148 kg H2 / L, respectively, which is twice the density of liquid hydrogen.
[0004] PMMA has good performance in improving the air stability of hydrogen storage materials. Studies have shown that the composite material composed of PMMA and metal hydride ball milling has good air stability. In terms of hydrogen release, the initial hydrogen release temperature of the hydrogen storage composite material is significantly reduced and the hydrogen release rate is significantly increased. Therefore, the AlH3-PMMA composite material has certain improvements in the initial hydrogen release temperature, hydrogen release rate and air stability. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a polymer-doped aluminum hydride hydrogen storage material and a preparation method thereof. The method for preparing the polymer-doped aluminum hydride hydrogen storage material prepared by the present invention has a simple process, is easy to control, has good controllability, and has a low additive cost. The material after ball milling is pressed into a disc shape under high pressure, which can effectively increase space utilization.
[0006] In order to achieve the purpose of the above-mentioned polymer-doped aluminum hydride hydrogen storage material, the present invention provides the following technical solution: The present invention provides a polymer-doped aluminum hydride hydrogen storage material, including a composite hydrogen storage material, wherein the composite hydrogen storage material is composed of a light metal hydride and a polymer, the light metal hydride includes at least one of LiH, MgH2 or AlH3, and the polymer includes at least one of PMMA, ABS or PVP.
[0007] Preferably, the mass ratio of the light metal hydride to the polymer is 1:0.1-100.
[0008] Preferably, the composite hydrogen storage material is composed of AlH3 and PMMA, and the composition expression of the composite hydrogen storage material is AlH3+x wt.%PMMA, wherein x represents the mass fraction of PMMA in the composite hydrogen storage material, and 1 <x<100。
[0009] Preferably, the value of x is 7.5.
[0010] Preferably, the preparation method comprises the following steps:
[0011] S1: In an inert gas atmosphere, metal hydride and polymer are placed in a ball mill in a certain ratio for mechanical ball milling to obtain a powdery composite material;
[0012] S2: The ball-milled composite material powder is subjected to high pressure curing treatment.
[0013] Preferably, the ball mill has a rotation speed of 100 to 500 rpm.
[0014] Preferably, the ball milling time is 0.1 to 100 hours.
[0015] Preferably, the inert gas includes one or more of nitrogen, argon or helium.
[0016] Preferably, the ball-to-material ratio in the ball milling process is 10 to 100:1.
[0017] Preferably, the curing pressure of the high-pressure curing treatment is 1-100 MPa, and the diameter of the pressed tablets of the high-pressure curing treatment is 1-100 mm.
[0018] Compared with the prior art, the present invention provides an aluminum hydride hydrogen storage material doped with rare earth oxide and a preparation method thereof, which has the following beneficial effects:
[0019] Since the hydrogen storage material is AlH3 doped with polymer PMMA, PMMA can be coated around AlH3 particles, and the HO bond of PMMA forms a chemical reaction with the H of AlH3, which makes it have a unique role in catalysis. The initial hydrogen release temperature of the aluminum hydride hydrogen storage material modified by the method is significantly reduced, which can be reduced from 140°C to 110°C. In addition, the air stability is also significantly enhanced. At the same time, the polymer PMMA used is low in cost and easy to obtain. By adopting a mechanical ball milling method to add additives, the addition process is simple and suitable for industrial large-scale production. In addition, the present invention also uses the material after ball milling to press the material into a disc shape under high pressure, which can effectively increase the space utilization rate. Therefore, the preparation method of the aluminum hydride hydrogen storage material doped with a polymer prepared by the present invention has a simple process, is easy to control, has good controllability, and has a low additive cost. The material after ball milling is pressed into a disc shape under high pressure, which can effectively increase the space utilization rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The X-ray diffraction diagram of the composite hydrogen storage material sample before dehydrogenation prepared in the embodiment of the present invention;
[0021] Figure 2 The hydrogen release amount-time curve of the prepared composite hydrogen storage material and the original AlH3 sample measured by constant temperature hydrogen release test at 100°C;
[0022] Figure 3 The hydrogen release amount-time curve of the prepared pressed composite material measured by the hydrogen release test at a constant temperature of 140°C. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present invention first provides a polymer-doped aluminum hydride hydrogen storage material, including a composite hydrogen storage material, wherein the composite hydrogen storage material is composed of a light metal hydride and a polymer, wherein the light metal hydride comprises at least one of LiH, MgH2 or AlH3, and the polymer comprises at least one of PMMA, ABS or PVP.
[0025] Furthermore, the mass ratio of the light metal hydride to the polymer is 1:0.1-100.
[0026] Further, the composite hydrogen storage material is composed of AlH3 and PMMA, and the composition expression of the composite hydrogen storage material is AlH3 + x wt.% PMMA.
[0027] Further, the mass ratio of the light metal hydride to the polymer is 1:0.1 - 100, where x represents the mass percentage of PMMA in the composite hydrogen storage material and 1 < x < 100. Further, the value range of x is 1 - 80, and more specifically, the value of x is 7.5.
[0028] Further, the preparation method includes the following steps:
[0029] S1: Under an inert gas atmosphere, put the metal hydride and the polymer into a ball mill in a certain proportion for mechanical ball milling, and a powdery composite material is obtained after ball milling.
[0030] S2: Perform high-pressure curing treatment on the ball-milled composite material powder.
[0031] And under an inert gas atmosphere, put the metal hydride and the polymer into a ball mill in a certain proportion for mechanical ball milling. After ball milling, a composite hydrogen storage material of aluminum hydride doped with PMMA is obtained, and high-pressure curing treatment is performed on the obtained composite hydrogen storage material. The obtained material is pressed into a circular sheet under high pressure.
[0032] Further, the rotation speed of the mechanical ball milling is preferably 100 - 500 rpm, and more preferably 200 - 400 rpm.
[0033] Further, the time of the mechanical ball milling is preferably 0.1 - 100 h, and more preferably 1 - 3 h.
[0034] Further, the inert gas in the mechanical ball milling is preferably one or more of argon, hydrogen, nitrogen, or helium. The inert gas is to ensure that AlH3 (aluminum hydride) and PMMA (polymethyl methacrylate) are in an inert atmosphere during the ball milling process. The type of the inert gas is not limited in the present invention.
[0035] Further, the ball-to-material ratio of the mechanical ball milling is preferably 10 - 100:1, and more preferably 40 - 60:1. It should be noted that those skilled in the art can set the ball milling speed, ball milling time, and ball-to-material ratio of the ball milling according to actual needs, and the present invention does not limit this here.
[0036] Further, the pressure required for high-pressure curing the material is preferably 1 - 100 MPa, and more preferably 1 - 10 MPa. The diameter of the tablet for high-pressure curing the material is preferably 1 - 100 mm.
[0037] Hereinafter, a polymer-doped aluminum hydride hydrogen storage material and a preparation method thereof of the present invention are described in detail through specific examples.
[0038] Example 1: In a nitrogen atmosphere, 9.75 g and 0.25 g of AlH3 and PMMA were weighed respectively according to the ratio of AlH3 + 2.5 wt.% PMMA, and evenly mixed in a nitrogen atmosphere. The total mass was 10 g. The evenly mixed sample was loaded into a ball mill, and steel balls (total mass 300 g) were added to the ball mill at a ball-to-material ratio of 30:1. The ball mill was then loaded into a 100 mL ball mill, and the ball milling speed was set to 350 rpm and the ball milling time was 2 h for mechanical ball milling. After the ball milling process was completed, the ball mill was taken out and the can was opened in a nitrogen atmosphere to collect the composite hydrogen storage material product.
[0039] Example 2: In a nitrogen atmosphere, 9.50 g and 0.50 g of AlH3 and PMMA were weighed respectively according to the ratio of AlH3 + 5wt.% PMMA, and evenly mixed in a nitrogen atmosphere. The total mass was 10 g. The evenly mixed sample was loaded into a ball mill, and steel balls (total mass 300 g) were added to the ball mill at a ball-to-material ratio of 30:1. The ball mill was then loaded into a 100 mL ball mill, and the ball mill speed was set to 350 rpm and the ball milling time was 2 h for mechanical ball milling. After the ball milling process was completed, the ball mill was taken out and the can was opened in a nitrogen atmosphere to collect the composite hydrogen storage material product.
[0040] Example 3: In a nitrogen atmosphere, weigh 9.25g and 0.75g of AlH3 and PMMA respectively according to the ratio of AlH3+7.5wt.%PMMA, and mix them evenly in a nitrogen atmosphere. The total mass is 10g. The evenly mixed sample is loaded into a ball mill, and steel balls (total mass 300g) are added to the ball mill at a ball-to-material ratio of 30:1. Then, the mixture is loaded into a 100mL ball mill, and the ball mill speed is set to 350rpm and the ball milling time is 2h for mechanical ball milling. After the ball milling process is completed, the ball mill is taken out and the can is opened in a nitrogen atmosphere to collect the composite hydrogen storage material product.
[0041] Experimental Example 4: In a nitrogen atmosphere, 9.0 g and 1.0 g of AlH3 and PMMA were weighed respectively according to the ratio of AlH3 + 10wt.% PMMA, and mixed evenly in a nitrogen atmosphere. The total mass was 10 g. The evenly mixed sample was loaded into a ball mill, and steel balls (total mass 300 g) were added to the ball mill at a ball-to-material ratio of 30:1. Then, the mixture was loaded into a 100 mL ball mill, and the ball mill speed was set to 350 rpm and the ball milling time was 2 h for mechanical ball milling. After the ball milling process was completed, the ball mill was taken out and the can was opened in a nitrogen atmosphere to collect the composite hydrogen storage material product.
[0042] Judgment criteria: In order to evaluate the hydrogen storage performance of the prepared composite hydrogen storage material, the ball-milled product was subjected to a constant temperature hydrogen desorption test at 100°C, and the corresponding hydrogen desorption amount was calibrated. The results of the constant temperature hydrogen desorption test at 100°C are as follows: Figure 2 As shown in the figure, the results show that PMMA significantly improves the dehydrogenation kinetics of α-AlH3. In addition, with the increase of dehydrogenation temperature, the modified composite material shows faster kinetic characteristics. At 100℃, the total hydrogen content released by the composite material is 3.5% in 30 minutes and 5% in 100 minutes, while the untreated AlH3 releases 0.5% hydrogen in 100 minutes. The XRD image measured before dehydrogenation is shown in Figure 2. Figure 1 As shown in the figure, by increasing the mass ratio of polymer PMMA, the generation of aluminum oxide in the material can be effectively reduced, which improves the hydrogen release efficiency of the composite material. Figure 1 The upright peach shape represents the curve of AlH3, and the inverted peach shape represents the curve of Al2O3.
[0043] pass Figure 1 It can be found that adding 10% PMMA can effectively prevent the composite material from being oxidized or hydrolyzed by oxygen and water vapor in the air. Since the production of aluminum oxide will form a solid oxide layer on the surface of aluminum hydride particles, when hydrogen begins to be released, it is difficult for hydrogen to break through the external oxide layer. Therefore, avoiding the formation of aluminum oxide can effectively increase the hydrogen release efficiency of the composite material.
[0044] according to Figure 2 The hydrogen release amount-time curve of the composite hydrogen storage material and the original AlH3 sample at 100°C constant temperature hydrogen release test. Figure 2 The diamond represents the curve of Pure α-AlH3, the circle represents the curve of As-milled α-AlH3, the inverted triangle represents the curve when the mass percentage of PMMA is 2.5%, the heart represents the curve when the mass percentage of PMMA is 5%, the five-pointed star represents the curve when the mass percentage of PMMA is 7.5%, and the regular triangle represents the curve when the mass percentage of PMMA is 10%. The AlH3+7.5wt.%PMMA component with the best hydrogen release performance is subjected to high-pressure curing treatment. 9.6g of the composite material and 0.4g of Al powder are weighed and mixed in a ball mill in a nitrogen atmosphere. Steel balls (total mass 300g) are added to the ball mill at a ratio of 30:1 between balls and materials. The ball mill is sealed in a nitrogen atmosphere, and the sealed ball mill is placed in a planetary ball mill for mechanical ball milling. The ball mill speed is 350rpm, and the ball milling time is 2h. After the ball milling process is completed, the ball mill is taken out and opened in a nitrogen atmosphere. The pressure is 4MPa for compression molding, and the hydrogen release test is waited.
[0045] In order to evaluate the hydrogen desorption capacity of the prepared tablet material, the constant temperature hydrogen desorption of the tablet material at 140°C was tested, such as Figure 3 As shown, Figure 3 The diamond in the middle represents the curve when no Al is added, the circle represents the curve when 2% Al is added, the inverted triangle represents the curve when 4% Al is added, the five-pointed star represents the curve when 6% Al is added, and the equilateral triangle represents the curve when 8% Al is added. Analysis shows that the figure is a tableting hydrogen desorption test with various proportions of Al added. Compared with the material without Al powder, the tableting material with Al powder added not only increases the amount of hydrogen desorption, but also increases the hydrogen desorption rate. Adding 6% Al powder can increase the amount of hydrogen desorption by 2.1%. It can be seen that the addition of different proportions of Al powder can significantly improve the amount of hydrogen desorption of the tableting material. At the same time, PMMA material can effectively slow down the rate of oxidation and hydrolysis of the tableting material by air, and then Al powder can be added to the prepared material to increase the amount of hydrogen desorption of the pressed tablet.
[0046] The beneficial effects of the present invention are:
[0047] Since the hydrogen storage material is a polymer PMMA doped in AlH3, PMMA can be coated around the AlH3 particles, and the HO bond of PMMA forms a chemical reaction with the H of AlH3, which makes it have a unique role in catalysis. The initial hydrogen release temperature of the aluminum hydride hydrogen storage material modified by the method is significantly reduced, which can be reduced from 140°C to 110°C. In addition, the air stability is also significantly enhanced. At the same time, the polymer PMMA used is low in cost and easy to obtain. By using a mechanical ball milling method to add additives, the addition process is simple and suitable for industrial large-scale production. In addition, the present invention also uses the material after ball milling to press the material into a disc shape under high pressure, which can effectively increase the space utilization rate. Therefore, the preparation method of the aluminum hydride hydrogen storage material doped with a polymer prepared by the present invention has a simple process, is easy to control, has good controllability, has a low additive cost, and the material after ball milling is pressed into a disc shape under high pressure, which can effectively increase the space utilization rate.
[0048] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polymer-doped aluminum hydride hydrogen storage material, characterized in that: The composite hydrogen storage material comprises a light metal hydride and a polymer, wherein the light metal hydride is AlH3, and the polymer comprises at least one of PMMA, ABS or PVP; The mass ratio of the light metal hydride to the polymer is 1:0.1-100; The preparation method of the polymer-doped aluminum hydride hydrogen storage material comprises the following steps: S1. In an inert gas atmosphere, metal hydride and polymer are placed in a ball mill in a certain proportion for mechanical ball milling to obtain a powdered composite material; S2, subjecting the ball-milled composite material powder to high pressure curing treatment; The curing pressure of the high-pressure curing treatment is 1-100 MPa, and the diameter of the pressed tablets of the high-pressure curing treatment is 1-100 mm.
2. The polymer-doped aluminum hydride hydrogen storage material according to claim 1, characterized in that: The composite hydrogen storage material is composed of AlH3 and PMMA. The composition expression of the composite hydrogen storage material is AlH3+x wt.%PMMA, wherein x represents the mass fraction of PMMA in the composite hydrogen storage material, and 1 <x<100。 3. The polymer-doped aluminum hydride hydrogen storage material according to claim 2, characterized in that: The value of x is 7.
5.
4. The polymer-doped aluminum hydride hydrogen storage material according to claim 3, characterized in that: The ball mill has a rotation speed of 100 to 500 rpm.
5. The polymer-doped aluminum hydride hydrogen storage material according to claim 4 is characterized in that: The ball milling time is 0.1 to 100 hours.
6. The polymer-doped aluminum hydride hydrogen storage material according to claim 5, characterized in that: The inert gas includes one or more of nitrogen, argon or helium.
7. The polymer-doped aluminum hydride hydrogen storage material according to claim 6, characterized in that: The ball-to-material ratio in the ball milling process is 10-100:1.
Citation Information
Patent Citations
Polymer-coated hydrogen storage material, preparation method and application thereof
CN112390224A
Cited By
Method for improving hydrogen absorption and desorption cycle performance and poison resistance of hydrogen storage alloy
CN121518967A
Composite hydrogen storage material and preparation method thereof
CN122426709A